Fungal decomposition of needles in pine plantations - Auer, Celso Garcia (2010)
A literature review was performed to discuss the fungal decomposition of needle pines and impacts on commercial forest production and sustainability. Aspects as organic matter and litter degradation, associated micobiota, and factors that condition this process are discussed. Needles are principal components of residues in pine forests and their decomposition by fungi is important to nutrient turnover. Nutrients released for soil by decomposition increases forest productivity which promotes more biomass production and fixation of carbon in trees.